The non-indigenous Paranthura japonica Richardson, 1909 in the Mediterranean Sea: travelling with shellfish? - MARCHINI, A.; SORBE, J. C.; TORELLI, F.; LODOLA, A.; OCCHIPINTI-AMBROGI, A. (Mediterranean Marine Science, 2014)
An anthurid isopod new to the Mediterranean Sea has recently been observed in samples from three localities of the Italian coast: the Lagoon of Venice (North Adriatic Sea), La Spezia (Ligurian Sea) and Olbia (Sardinia, Tyrrhenian Sea). The specimens collected showed strong affinity to a species originally described from the NW Pacific Ocean: Paranthura japonica Richardson, 1909. The comparison with specimens collected from the Bay of Arcachon (Atlantic coast of France), where P. japonica had been recently reported as non-indigenous, confirmed the identity of the species. This paper reports the most relevant morphological details of the Italian specimens, data on the current distribution of the species and a discussion on the pathways responsible for its introduction. The available data suggest that the presence of this Pacific isopod in several regions of coastal Europe might be due to a series of aquaculture-mediated introduction events that occurred during the last decades of the 1900s. Since then, established populations of P. japonica, probably misidentified, remained unnoticed for a long time.